PENCEGAHAN STUNTING, ANTI NARKOBA, DAN GERAKAN PEDULI LINGKUNGAN: PRAKTIK NYATA PENGABDIAN MAHASISWA KKN DI KELURAHAN LAKAHANG MAMASA - Abdul Wahab; Kurnia, Kurnia; Yati Heriyati; Furqan, Furqan; Muh. Sibgatullah (Bajang Institute, 2025)
The Community Service Program (Kuliah Kerja Nyata / KKN) is one of the main pillars of higher education’s Tri Dharma that emphasizes direct community engagement. The 5th KKN program of Muhammadiyah University of Mamuju was conducted in Lakahang Village, Tabulahan District, Mamasa Regency, focusing on three strategic issues: stunting prevention, drug abuse prevention, and environmental awareness campaigns. The primary objective was to provide practical solutions to health, social, and environmental problems faced by the community, while simultaneously enhancing students’ social sensitivity and problem-solving skills. The program was implemented through participatory, educational, and collaborative approaches involving field observation, health counseling, awareness campaigns, practical demonstrations, community clean-up activities, and mentoring. The results showed an increase in mothers’ knowledge of balanced nutrition and child care during the first 1,000 days of life, the establishment of the “Lakahang Youth Anti-Drug Community” as a platform for youth empowerment, and greater public awareness of environmental cleanliness through the creation of simple waste bins and routine “Friday Clean-Up” activities. These findings confirm that KKN-based community service can make a tangible contribution to improving community well-being, fostering collective awareness, and strengthening the role of students as agents of social change.